ANALYSIS OF GREEN EMPOWERMENT, CAREER OPPORTUNITIES, EMPLOYEES TEAMWORK AND WORK SATISFACTION TOWARD JOB PERFORMANCE IN PT. ABC GENERAL CONTRACTOR COMPANY IN SIDOARJO - Hananiel Gunawan; Priscilla Napitupulu; Janice Siahaya (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
The transition towards sustainable business practices has led to the increasing importance of job performance, which is influenced by various organizational and individual factors. This study analyses the impact of Green Empowerment, Career Opportunities, Employees’ Teamwork, and Work Satisfaction on Job Performance. These factors are essential in fostering an environmentally responsible workforce, ensuring that sustainability goals align with organizational and employee objectives. Contractor industry is one of the good examples of how job performance should be applied focusing on green aspect. The performance of general contractor companies plays a crucial role in the success of construction projects and influencing cost efficiency. Using a quantitative approach, data was collected from employees working in environmentally conscious organizations and analyzed using SPSS software statistical tool. This research explores how Green Empowerment, which involves providing employees with autonomy and resources to implement sustainable practices—affects job performance. Additionally, Career Opportunities may serve as motivation for employees to commit to environmental initiatives within their organizations. The study also examines the role of Employees’ Teamwork in fostering a shared responsibility for sustainability efforts. Furthermore, Work Satisfaction is considered as a factor that may enhance employees' commitment and job performance. By investigating these relationships, this study aims to contribute to the growing literature on green human resource management and provide insights into strategies that organizations can adopt to enhance Job Performance. The findings of this research can help businesses develop more effective sustainability policies and improve their overall environmental impact.